Exergy analysis and energy utilization in the transportation sector of the Philippines - Buenafe, R. J. Q. (Animo Repository, 2020)
This paper analyzed the energy and exergy utilization of the four transportation sectors (road, rail, water, and air) in the Philippines during the years 1990 to 2016. The consumption per fuel was also considered in the analysis because each sector utilizes one or more type of fuel. The collected data showed that road transportation has the highest fuel utilization, and energy and exergy efficiency amongst the four followed by the aviation and marine subsectors which are both less significant than the results from the road transportation sector. Also, it was observed that diesel and gasoline are the ones commonly used in the road, rail, and marine subsectors compared to LPG, ethanol, biodiesel, and electricity. Comparing the overall energy and exergy efficiencies from 20 years ago, it was observed that the efficiencies are gradually increasing annually in small increments. The data presented in this research will be beneficial to the Philippine transportation sector to effectively reduce cost and improve the quality of transport in the country. It is also helpful to base future transportation designs on the energy and exergy efficiencies to better improve transportation and reduce the environmental impact which can both be practical for the economy and the ecosystem. © 2020 IOP Publishing Ltd.